ANALYSIS OF MARKETING STRATEGY THROUGH SOCIAL MEDIA ON UNIVERSITY STUDENTS' PURCHASE INTENTION IN PURCHASING SMARTPHONES AT TRICOMSEL GUNUNGSITOLI - Fedianus Giawa; Yuterlin Zalukhu; Edward Harefa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Social media users are increasing and influencing the world of marketing, even the use of social media as a marketing tool is considered a trendsetter. This study aims to analyze the effect of social media marketing on university students' purchase intention in smartphones sold at Tricomsel Gunungsitoli. This study was carried out using quantitative data, with a questionnaire containing 20 questions and being distributed to 85 survey university students who had made at least one smartphone purchase from the Tricomsel Gunungsitoli store. Utilizing the slovin formula, researchers employed the sampling technique of random selection. The purpose of this study's data analysis was to test hypotheses using validity and reliability testing. The results of the regression analysis demonstrate a very significant and statistically significant correlation between social media and consumers' purchasing interest by 73.7%. Researchers recommend that store to keep improving the marketing strategy through social media